How late-modern nomads imagine tomorrow? A Causal Layered Analysis practice to explore the images of the future of young adults - Seyedeh Akhgar Kaboli; Petri Tapio (Elsevier, 2022)
Images of the future represent fears, hopes and anticipations humans have for the future. Understanding the images of the future of young people provides a beneficial source of information not only about their probable future actions but also about their current motivations, decisions and choices. This article describes the procedure of exploring the images of the future of a group of young adults from different cultural backgrounds who are Bachelor and Master’s degree students in Finland. Due to the intricate nature of the images of the future and also the existent complexity within the current societal context, this study proposes that investigation of the images of the future demands a refined, subtle selection of methods. During this study, a combination of several interview techniques is employed to collect the qualitative research material. Then Causal Layered Analysis (CLA) is utilized as a multi-layered theoretical framework for qualitative content analysis of the material. The results include four images of the future which reflect on different levels of the young adults’ understandings and feelings. The first image, Living With the Chill, displays the most pessimistic view of the future and the fourth, Imagine…!, is the most optimistic one. Two other images, Fear and Hope, and Life as a Chance for Dedication, are moderate, not very optimistic, nor very pessimistic. The images of the future of the participants of this study suggest that young adults tend to define the future in terms of presence or absence of the current societal concerns and do not seem to exceed this framework. They also indicate that the studied young adults’ radically negative or positive approach toward the future have reduced their perceived locus of control. We conclude that using CLA in the analysis of interview material produces a fruitful, rich, in-depth understanding of the images of the future.